(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The work presents comparative study of wind forces on high rise buildings for different analytical methods. As the height of the structure goes on increasing wind forces start predominating over earthquake forces which require proper assumption of force factors in order keep structure safe & serviceable. The reason for knowing exact wind force behavior and values is to identify and keep parameters such as the base shear, storey displacement, storey drift, overturning moment and story shear within permissible limits of serviceability. As Comparisons of the wind forces obtained by Indian codal provisions & wind tunnel are presented for some representative cases to gaze the relative level of protection attributed by Indian wind codes. This study includes wind forces obtained by force coefficient based static analysis and gust factor based dynamic analysis. Experimental comparative study of wind force conducted on two of the high rise buildings from Mumbai metro city for static and dynamic codal provisions & wind tunnel observations. The analysis performed on this building to identify above factors by using software’s package i.e. Etabs & wind tunnel laboratory data.